Modeling of kayak athletes competition activity - Kolumbet, A. N.; Dudorova, L. Y.; Babina, N. A.; Bazulyuk, T. A.; Chernovsky, S. M. (Physical Education of Students, 2017)
Purpose: determination of correlations between parameters of special and technical fitness of kayak athletes on 500 meters` distance. Material: in the research 29 elite athletes participated. We studied characteristics of athletes` coordination structure in natural conditions and laboratory experiment. Results: significant influence of specific adaptive reactions on workability dynamic and sport results is noted. Constant reduction of power is connected with lactate, pyruvate and other under-oxidation products` accumulation in athlete`s muscles. 500 meters` distance passing in alternative regime of motor activity permits for athletes to achieve higher level of special workability. We studied four variants of 500 meters` competition distance passing. Most of athletes pass this distance by third variant (46% of all tested athletes) 21% - by the first variant; 14% - by second variant and 19% by the forth. Conclusions: achievement of high sport result is facilitated by optimal structure of competition functioning, which corresponds to the following: speed power qualities and special endurance; individual features of athletes; specific of physical qualities` manifestation, when passing definite distance.